(untitled) (Research, Society and Development, 2021)
Accessibility for the deaf in spaces of scientific dissemination is a right guaranteed by law but little implemented. This participatory research of qualitative approach aimed to present the process of developing guide videos for itinerant science centers and the strategies used to solve the identified problems, as well as to analyze the opinion of the deaf about the material developed. For this, we produced guide videos in Libras and presented them to a group of 30 deaf people to evaluate the following: explanation, content, interpretation and background color. The evaluation of the deaf public showed us that it is important to develop strategies to facilitate the understanding of what is being explained since there are linguistic variations within Libras and different levels of linguistic acquisition. Two of the strategies we used and were well accepted by the deaf to solve this issue were the use of subtitles and illustrative images. Another strategy suggested by the deaf was greater use of the imagery description, a feature widely used by the deaf and that helps to create a visual image of what is being explained. We also found that the best accepted background colors were blue and green, and that black and white colors should be made available as optional to meet people with some visual impairment. We conclude that the guide videos achieved the objective of transmitting the information and had good acceptance by the deaf public and, therefore, it is appropriate to implement them in itinerant science centers that rely on volunteer work.